2016
DOI: 10.1111/jsr.12428
|View full text |Cite
|
Sign up to set email alerts
|

New hypothesis on pontine–frontal eye field connectivity in Kleine–Levin syndrome

Abstract: Previous studies have indicated involvement of the thalamus and the pons in the KleineLevin syndrome. In the present study, we investigated functional connectivity of the thalamus and the pons in asymptomatic Kleine-Levin syndrome patients and healthy controls. Twelve patients and 14 healthy controls were investigated by functional magnetic resonance imaging during rest. Resting state images were analysed using seed regions of interest in the thalamus and the pons. Results showed significantly lower functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…However, asymptomatic KLS patients as compared with healthy controls showed no difference in thalamic connectivity during rest. In addition, KLS patients had significantly reduced functional connectivity between dorsal pons and the frontal eye field; an area of the brain not only involved in cerebral control of eye movements but also involved in attention and working memory (Engström and others 2016). Given the lack of evidence, further neuroimaging research investigating brainstem involvement in KLS is warranted.…”
Section: Clinical Features and Pathogenesis Of Klsmentioning
confidence: 99%
“…However, asymptomatic KLS patients as compared with healthy controls showed no difference in thalamic connectivity during rest. In addition, KLS patients had significantly reduced functional connectivity between dorsal pons and the frontal eye field; an area of the brain not only involved in cerebral control of eye movements but also involved in attention and working memory (Engström and others 2016). Given the lack of evidence, further neuroimaging research investigating brainstem involvement in KLS is warranted.…”
Section: Clinical Features and Pathogenesis Of Klsmentioning
confidence: 99%
“…In the literature search, we found 12 original articles on neuroimaging in KLS published 2013–2018, whereof five articles were case reports [ 7 , 8 , 9 ••, 10 18 ] (Table 1 ). Most studies report deviant function in the form of hypoperfusion, glucose hypermetabolism, or increased BOLD responses in frontotemporal areas (Fig.…”
Section: Recent Neuroimaging Findings In Klsmentioning
confidence: 99%
“…No difference in thalamic connectivity. Engström et al , 2016 [ 9 ••] FDG-PET 1 KLS Symptomatic Decreased glucose metabolism in bilateral thalami. Xie et al , 2016 [ 10 ] SPECT 41 KLS, 15 HC Symptomatic and asymptomatic General hypoperfusion in hypothalamus, thalamus, caudate, and anterior cingulate, orbito-frontal and temporal cortices.…”
Section: Recent Neuroimaging Findings In Klsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area here identified as SMA is identical with the supplementary eye field according to a meta-analysis on saccades by Jamadar et al ( Jamadar et al, 2013 ) . A recent study by us also found brainstem-frontal eye fields connectivity differences between patients with periodic idiopathic hypersomnia, the Kleine-Levin Syndrome (KLS), and healthy controls (Engstrom et al, 2016). The eventual implications of the oculomotor system in patients with sleep disorders have to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 78%